The Education about Breakfast and its Importance Given to Child-to-Mother in Turkey - Sahingoz, Semra Akar (Pakistan Journal of Nutrition, 2009)
This study was planned to give education to children in primary education and their mothers through their children on breakfast and its importance and to determine the efficiency of this education method in Turkey. The schools were classified as groups of experiment and control. A questionnaire form was prepared in order to determine the nutrition levels of the students and their mothers and this form was applied as pre-test and post-test. The research was conducted on 31 students between ages of 11-13 and their mothers in two private primary schools. When education was given, education techniques such as research and discussion, illustrated explanation, role-playing, painting, poster design, lyrics writing and composing and poem-writing were enjoyed. Non-parametrical test of Wilcoxon Matched-Pairs Signed-Ranks Test and Independent-Samples t-test were also used. It has been determined in the outcome of the educational activities conducted that there is a significant difference (p